2020
DOI: 10.1002/uog.20302
|View full text |Cite
|
Sign up to set email alerts
|

Fetal echocardiographic prediction score for perinatal mortality in tricuspid valve dysplasia and Ebstein's anomaly

Abstract: Objectives Tricuspid valve dysplasia (TVD) and Ebstein's anomaly (EA) diagnosed by fetal echocardiography vary greatly in terms of clinical severity and prognosis. The Celermajer index and Simpson–Andrews–Sharland (SAS) score have been reported previously for the prediction of prognosis in cases of TVD/EA; however, they do not take into account the hemodynamic impact of left ventricular (LV) function, which has recently been implicated as being important in the pathophysiology of TVD/EA. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 12 publications
2
24
0
2
Order By: Relevance
“…Different echocardiographic parameters have been correlated with perinatal mortality in EA, such as reverse flow in the ductus arteriosus and pulmonary insufficiency [3, 15]. However, the results of the largest available multicenter study [3] do not fully correspond to our series (Table 2).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Different echocardiographic parameters have been correlated with perinatal mortality in EA, such as reverse flow in the ductus arteriosus and pulmonary insufficiency [3, 15]. However, the results of the largest available multicenter study [3] do not fully correspond to our series (Table 2).…”
Section: Discussionmentioning
confidence: 71%
“…Based on these results, the authors proposed a new severity score, which included the CTR, the TV annulus diameter z -score, and the presence of pulmonary regurgitation, none of which achieved the necessary significance to remain in our logistic regression model. Additionally, 2 new scoring systems have also been proposed recently: the TRIPP score (TRIcuspid malformation Prognosis Prediction score) [15] and the SickKids score [11]. Since the TRIPP score included the LV Tei-index, combined with the presence of TR and the flow characteristics in the pulmonary artery and ductus arteriosus, we could not validate it in our series.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…16,24 A new study in 2020 found left ventricular (LV)-Tei index is significantly related to perinatal death of EA/TVD fetuses. 24 Therefore, it is clinically relevant to evaluate and monitor cardiac function in TVM fetuses, which may facilitate parental counseling and perinatal management.…”
mentioning
confidence: 99%